2010
DOI: 10.1097/ajp.0b013e3181e15b98
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms and the Diathesis-Stress Model of Chronic Pain and Disability in Patients Undergoing Major Surgery

Abstract: Objectives: To (1) use structural equation modeling (SEM) to examine relationships proposed in Turk's diathesis-stress model of chronic pain and disability as well as (2) investigate what role, if any, posttraumatic stress symptoms (PTSS) play in predicting pain disability, relative to some of the other factors in the model. Methods:The study sample consisted of 208 patients scheduled for general surgery, 21 to 60 years of age (mean age= 47.18 y, SD = 9.72 y), who reported experiencing persistent pain for an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 62 publications
5
47
0
1
Order By: Relevance
“…Therefore, absolute fit indexes -χ 2 and Root Mean Square Error of Approximation (RMSEA) were used to determine how well the apriori model fit the data [25]. Also, incremental fit indexes -Incremental Fit Index (IFI), the Normed Fixed Index (NFI) and the Comparative Fit Index (CFI) indicated the fit of the model when compared to the baseline model [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, absolute fit indexes -χ 2 and Root Mean Square Error of Approximation (RMSEA) were used to determine how well the apriori model fit the data [25]. Also, incremental fit indexes -Incremental Fit Index (IFI), the Normed Fixed Index (NFI) and the Comparative Fit Index (CFI) indicated the fit of the model when compared to the baseline model [15].…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the impact of PSS on pain and pain-related disability might depend on the extent to which it is promoting functional autonomy versus dependence [26]. Our contention is based on the assumptions that: 1) avoidance behaviors represent a main predictor of functional disability in CP, as postulated by fearavoidance [21,39,20] and diathesis-stress models [37,25]; 2) PSS, by promoting functional autonomy or dependence, may influence the extent to which individuals engage in activity avoidance versus engagement.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work (Matos, et al, 2015), we established that the ability to perform daily activities -physical functioning -was positively associated with perceived promotion of autonomy and negatively associated with perceived promotion of dependence. As low physical functioning has been associated with painrelated disability (e.g., Leeuw et al, 2007;Lethem et al, 1983;Martin et al, 2010;Turk, 2002;Vlaeyen et al, 1995), we wanted to investigate whether the level of physical functioning could be a mechanism through which perceived promotion of autonomy and dependence would be related to pain-related disability. Thus, the second aim of the present study was to explore the mediating role of self-reported physical functioning in the relationship between perceived promotion of autonomy and dependence and pain-related disability, in older adults with chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…[164][165][166][167] Recognizing the importance of pain-related fear and anxiety in the transition to chronicity, this section describes how these constructs may be relevant to the experience of acute and chronic pain and their impact on physical function in post-surgical patients.…”
Section: Fear Anxiety and Pain After Surgerymentioning
confidence: 99%